Tropical gastropod density and diversity in the mangrove forest of Totobo Village, Southeast Sulawesi, Indonesia - MUHAMMAD FAJAR PURNAMA; SLAMET B. PRAYITNO; MAX R. MUSKANANFOLA; SURYANTI SURYANTI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Purnama MF, Prayitno SB, Muskananfola MR, Suryanti. 2024. Tropical gastropod density and diversity in the mangrove forest of Totobo Village, Southeast Sulawesi, Indonesia. Biodiversitas 25: 1663-1675. The mangrove ecosystem of Totobo Village, Southeast Sulawesi, is a habitat for various species of edible and economically important gastropods. This research aims to determine mangrove gastropods' density and ecological index (diversity). This research was carried out from June to September 2023 in the mangrove ecosystem of Totobo. This research adopts purposive sampling and systematic random sampling techniques to determine stations and place the distribution of sampling points (sub-stations). The gastropod sample collection was done using the handpicking method or manually. More than 34 species of gastropods (14 families and 24 genera) were found in the mangrove ecosystem of Totobo. The diversity index (H' = 3.07) of gastropods in the Totobo mangrove ecosystem is directly proportional to the species richness value (R = 4.43), which is in the high category. The evenness index is in the medium category (E = 0.89), and the dominance index (C) has a value of 0.01, meaning no dominance of a particular species. The condition described is a representation of a system of homeostasis or environmental balance that is currently being maintained. This directly impacts the optimal biological activity (physiology) of the gastropod community and other aquatic organisms in the mangrove ecosystem (estuary) of Totobo Village.